Lettuce in Monoculture or in Intercropping with Tomato Changes the Antioxidant Enzyme Activities, Nutrients and Growth of Lettuce - Cunha-Chiamolera, Tatiana P. L.; Cecílio Filho, Arthur Bernardes [UNESP]; Santos, Durvalina M. M. [UNESP]; Chiamolera, Fernando M.; Guevara-González, Ramón G.; Nicola, Silvana; Urrestarazu, Miguel (MDPI, 2023)
Intercropping systems are a widely used agricultural practice by smallholder farmers to enhance food security and to use natural resources more efficiently. The objective of this study was to evaluate two lettuce cvs under an intercropping system. Enzymatic growth, yield and economic benefit were evaluated. The experiment was carried out from August to February in Jaboticabal (Brazil) using tomato plants as a main crop and Lucy Brown and Vanda cvs of lettuce as secondary crops. The catalase, superoxide dismutase and peroxidase activity of lettuce plants was analyzed. Mineral nutrient content, growth, yield parameters and commercial economic benefit were measured. Significant differences in stress and activity enzymatic indicators were found versus cultivars of lettuce. The loss of abiotic factors such as radiation or its effect on enzymatic stress indicators was greater than its effect on yield. Yield loss in the intercropping systems was different for each cultivar system, with cv Lucy Brown showing greater yield loss than cv Vanda. Economic benefit was only found for the Vanda lettuce cv. Although the benefits of intercropping have been demonstrated as very appropriate cultural management, the choice of cultivars involved might be the determining factor for the agronomic success of the system.
Keywords: coir fiber substrate; Lactuca sativa; oxidative stress; shading; soilless culture; yield